Inhibition of Phosphoinositide-3-Kinase Signaling Promotes the Stem Cell State of Trophoblast. (18th July 2019) - Lee, Cheryl Q.E.; Bailey, Alexander; Lopez-Tello, Jorge; Sferruzzi-Perri, Amanda N.; Okkenhaug, Klaus; Moffett, Ashley; Rossant, Janet; Hemberger, Myriam
Abstract: Trophoblast stem cells (TSCs) are a heterogeneous cell population despite the presence of fibroblast growth factor (FGF) and transforming growth factor β (TGFB) as key growth factors in standard culture conditions. To understand what other signaling cascades control the stem cell state of mouse TSCs, we performed a kinase inhibitor screen and identified several novel pathways that cause TSC differentiation. Surprisingly, inhibition of phosphoinositide-3-kinase (PI3K) signaling increased the mRNA and protein expression of stem cell markers instead, and resulted in a tighter epithelial colony morphology and fewer differentiated cells. PI3K inhibition could not substitute for FGF or TGFB and did not affect phosphorylation of extracellular signal-regulated kinase, and thus acts independently of these pathways. Upon removal of PI3K inhibition, TSC transcription factor levels reverted to normal TSC levels, indicating that murine TSCs can reversibly switch between these two states. In summary, PI3K inhibition reduces the heterogeneity and seemingly heightens the stem cell state of TSCs as indicated by the simultaneous upregulation of multiple key marker genes and cell morphology. Stem Cells 2019;37:1307–1318 : Abstract : Trophoblast stem cells are heterogeneous in culture, with variable expression levels of key trophoblast stem cell genes. Upon phosphoinositide-3-kinase inhibition, trophoblast stem cells become more homogeneous and exhibit increased expression levels of trophoblast stem cell genes. We propose that phosphoinositide-3-kinase signaling modulates the stem cell state of trophoblast stem cells.